Dynamics of Carbon Storage in Saltmarshes Across China’s Eastern Coastal Wetlands From 1987 to 2020 - Li, Jingtai; Yan, Dandan; Yao, Xiuying; Liu, Yao; Xie, Siying; Sheng, Yufeng; Luan, Zhaoqing (Frontiers in Marine Science, 2022)
Saltmarsh carbon storage contributes significantly to combating global climate change and achieving regional carbon neutrality. Yet saltmarsh carbon stocks have shown a trend of decline in recent years. Therefore, long-term monitoring and analyzing of saltmarshes for their carbon storage is imperative to better protect and manage this pool of carbon. This study investigated the spatiotemporal dynamics in saltmarsh carbon storage during 1987–2020, by using the Google Earth Engine (GEE) platform and applying the Integrated Valuation of Ecosystem Services and Tradeoffs (InVEST) model, and analyzed the driving factors of carbon storage in saltmarshes. The key results are as follows. Firstly, carbon density values in saltmarshes ranged more than 14-fold, from 7.24 to 104.99 Mg·hm-2, and the total carbon storage showed a decreasing trend. Secondly, reduced carbon storage was concentrated in inshore saltmarshes adjacent to reclamation sites, especially in Shandong, whereas augmented carbon storage characterized the offshore saltmarshes dominated by Spartina alterniflora, especially in Shanghai and Jiangsu. Overall, the carbon stocks of saltmarshes have fallen by 10.44 Tg; the decrease in carbon storage caused by Suaeda salsa, Phragmites australis, and mudflats exceeded the increase in carbon storage caused by Spartina alterniflora and Scirpus mariqueter. Further, we found that reclamation was the most dominant driver of carbon storage reductions, except for sea level rise and hurricane disturbances that can also negatively impact carbon storage, while greater carbon storage was closely related to the invasion of Spartina alterniflora. This study’s findings facilitate the development of a carbon storage management strategy for saltmarsh ecosystems to address global climate change and contribute to attaining carbon neutrality.